Hubungan Pengetahuan Tentang Hipertensi Dan Dukungan Keluarga Terhadap Asupan Natrium Penderita Hipertensi Rawat Jalan Di Rsud Sukoharjo - IDA UMAMI, FARA, Dyah Widowati, SKM, Nur Lathifah Mardiyati, S.Gz., M.S (2015)
Introduction: Hypertension is a disease which is characterized by the increasing blood pressure from normal. The prevalence of hypertension increase severy year and becomes the attention in developing countries, including in Indonesia. Risk factors hypertension of that can no difred are obesity, smoking, stress, sodium intake, physical activity and food consumption patterns. While factors that affect sodium intake are demographics, knowledge, family support and therapeutic communication. Objective: to find out the relationship knowledge about between hypertension family support of sodium intake toward hypertension patients in the regional public hospital of Sukoharjo. Research Method: This research was an observational study with cross sectional design. Sampling method used of consecutive sampling and obtained 45 subjects. Collected trough on knowledge about hypertension and family support are questionnaires, while sodium intake used food frequency form. The relationship tests were done using Spearman Rank tests. Results: respondens knowledge about hypertension was mostly good (57.8%) most of respondens (62.2%) also had good family. Number of respondens who had good sodium intake was 44.4%. The statistical test showed that there was no correlation between knowledge about hypertension and the sodium intake of hypertension patients, with values (p = 0671), and there was no correlation between family suport and sodium intake of hypertension patients (p = 0.542) Conclusion: There no correlation between knowledge about hypertension and family suports on the sodium intake toward hypertension patients in the regional public hospital of Sukoharjo Keywords: knowledge, hypertension, family support, sodium intake. Bibliography: 28 (1997 - 2013)